Issues in the diagnosis of SLI in Cypriot Greek bilingual children - Theodorou, Eleni; Kambanaros, Maria; Grohmann, Kleanthes K. (My University, 2012)
It is important to investigate children’s language skills in their native linguistic variety because diagnosis, and intervention (therapy), cannot be based on findings from other languages or varieties which have different properties. Likewise, all first language assessments must be appropriate for children who acquire their native variety — in the present study, Cypriot Greek (CG). This paper assesses the utility of existing tools in the diagnosis of specific language impairment (SLI) in CG. In total, 16 children with SLI ranging from 5 to 9 years of age and 22 age-matched typically developing children participated in this study. Results showed that the existing tools can be used to identify children with SLI, but only when the comparison is between children that use the same variety. However, a proper adaptation to CG is needed, given that due to cultural and linguistic differences, not all the stimuli from the Standard Greek versions were equally appropriate for Greek Cypriot children, who are here termed bilectal in the two linguistic varieties.
Keywords: Children; Language skills; Native linguistic variety; Language impairment; Cypriot Greek